Conceptual Design : A Critical Element of a Successful Government Financial Management Information System Project - Khan, Abdul (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This technical note describes need of conceptual design as a critical element of a government financial management information system project. Governments are increasingly turning to computerized financial management systems to help them respond to the demand for better information. This note describes the conceptual design for government financial management information systems (GFMIS), and explains why is it critical to the success of a GFMIS project. Key factors that influence the preparation of the conceptual design are discussed. The main stakeholders in the preparation of the conceptual design are also elaborated.